Prevalence of alcohol use among high school students, the pattern of consumption and the physical circumstances associated with alcoholism in an urban area of Kerala, India - S. S., Mini; U., Anuja; S., Shaheer Khan; K., Shameel K. (International Journal Of Community Medicine And Public Health, 2017)
Background: The present study was conducted to estimate the prevalence of alcoholism among high school students, the pattern of consumption and the physical circumstances lead them to alcoholism. Methods: This study was done as a cross sectional study in the high schools of Pagappara PHC area which is the urban health training centre attached to Government medical college Thiruvananthapuram, Kerala, India. Sample size was calculated based on the prevalence of a previous study conducted in Kottayam district Kerala and estimated as 300. Data was collected using a pre tested questionnaire through interview technique. Data entry was done in SPSS 16 and percentages were calculated to express the results. Results: The prevalence of drinking among the high school students was 21% and 1% of students were regular drinkers. Among those consumed alcohol 38.15 have used it before the age of 10 years. 61.9% started drinking for experimentation and beer was commonly used type (71%). Conclusions: According to this study 21% of students have consumed alcohol and 1% is regular users of alcohol. Thus, there is a dire need to intervene.